2015
DOI: 10.1097/brs.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

Primary Versus Revision Surgery in the Setting of Adult Spinal Deformity

Abstract: Relative to primary cases, those undergoing revision correction of spinal deformity have a higher risk of many procedure-related complications with a longer hospital course despite similar baseline comorbidity burden and the in-hospital mortality rate. This study provides clinically useful data for surgeons to educate patients at risk for morbidity and mortality and direct future research to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…In general, revision surgeries are not associated with improved pain scores and have a higher rate of comorbidities including increased bleeding, infections, acute respiratory distress syndrome, and longer hospital stays and even have higher mortality rates than the primary surgeries 43. Careful consideration of the type of therapy most appropriate for the treatment of FBSS is dependent on the etiology of the pain, likelihood that the intervention will succeed and the associated risks with the procedure.…”
Section: Management Of Fbssmentioning
confidence: 99%
“…In general, revision surgeries are not associated with improved pain scores and have a higher rate of comorbidities including increased bleeding, infections, acute respiratory distress syndrome, and longer hospital stays and even have higher mortality rates than the primary surgeries 43. Careful consideration of the type of therapy most appropriate for the treatment of FBSS is dependent on the etiology of the pain, likelihood that the intervention will succeed and the associated risks with the procedure.…”
Section: Management Of Fbssmentioning
confidence: 99%
“…In a study of 10,912 patients from the National (Nationwide) Inpatient Sample (NIS) database who underwent all types of spinal fusions, the incidence of procedure-related complications was approximately 30% higher for patients who underwent revision surgery than for primary cases. 6 This study also suggested that patients undergoing revision surgery are at specific increased risk of complications involving the nervous system, hematoma formation, vascular injury, nerve puncture, wound dehiscence, infection, and acute respiratory distress syndrome. 6 Similarly, in a study of ASD patients who underwent surgery for adult scoliosis, revision patients were found to have a higher overall complication rate than primary patients (58.2% vs 45.2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…6 This study also suggested that patients undergoing revision surgery are at specific increased risk of complications involving the nervous system, hematoma formation, vascular injury, nerve puncture, wound dehiscence, infection, and acute respiratory distress syndrome. 6 Similarly, in a study of ASD patients who underwent surgery for adult scoliosis, revision patients were found to have a higher overall complication rate than primary patients (58.2% vs 45.2%, respectively). 5 Results from other studies have suggested that there are no differences in morbidity and complication risk between primary and revision surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 On the other hand, given that the NIS is only an inpatient database, complications that may occur outside the hospital are not captured. Despite these limitations, various studies have examined short-term outcomes after scoliosis surgery using the NIS, 4,13,14,21 and most of their findings have been consistent with other multicenter collaborations, particularly in regard to rates of perioperative complications. Nonetheless, the findings in the present study may lead to future multicenter prospective studies on the matter, with longer-term follow-ups and patientreported outcomes.…”
Section: Discussionmentioning
confidence: 99%